HUBUNGAN KELENGKAPAN SARANA PRASARANA DENGAN HASIL BELAJAR KEARSIPAN SISWA DI SMKN 2 PADANG - Kuntum Khairiah Ummi; Zulmuqim Zulmuqim (UIN Imam Bonjol Padang, 2023)
This paper is motivated by the relationship between the completeness of infrastructure and the results of student archiving learning at SMKN 2 Padang. This study aims to determine whether there is a relationship between the completeness of infrastructure and the results of student archiving learning at SMKN 2 Padang. This research uses descriptive quantitative method. Questionnaires were distributed to 35 students at SMKN 2 Padang. The findings show that the determination value (R2) is 11,970, meaning that the relationship between the completeness of infrastructure and the results of student archiving learning at SMKN 2 Padang is 11.97%, the remaining 88.03% is caused by instrumental factors consisting of teaching media, teachers, learning materials and teaching and learning strategies.